Social inequalities in Morocco and the imperative of financing: What tax policy for the new development model? - ETTAHIRI , Lahcen; BENAZZOU , Lotfi (Revue du contrôle, de la comptabilité et de l’audit, 2022)
As part of the national reflection on the new dynamic development model to reduce social inequalities and in view of the repercussions of the covid-19 epidemic, the question of its financing is at the heart of the concerns of the Moroccan authorities. In this respect, thinking about a financing strategy through an efficient and adapted tax policy comes from its crucial role in the redistribution of wealth in order to reduce social inequalities. Nevertheless, the Moroccan tax system suffers from a number of dysfunctions and shortcomings that make it unfit to meet the challenges and objectives of the new development model. The aim of this research is to present, on the one hand the imperfections of our tax system, which are sources of tax injustice, and on the other hand to emphasize the important role of fiscal policy in reducing social inequality and financing the economic and social development of our country.